Exploring the livelihood strategies of unemployed black female migrant youth living in Cape Town, South Africa - Soko, Mumba Martha (Department of Social Development, 2021)
Unemployment among youth within the Southern African Development Community (SADC) region is one of the major factors that has contributed to migratory movements. Today many youths are leaving their home countries within the region, in search of employment opportunities in stronger economies like that of South Africa. However, the local unemployment rates hinder their chances of employment. This qualitative study explored the livelihood strategies of unemployed black female migrant youth living in Cape Town, South Africa. The study interviewed twenty unemployed black female migrant youth between the ages of 25 and 34 to understand their experiences and perceptions of a) factors or conditions that forced them to immigrate to Cape Town, b) challenges they encountered in trying to secure employment, and vulnerabilities experienced, and c) the livelihood strategies they employed and available social service support. The findings reveal that unemployed black female migrant youth have immigrated to Cape Town for various reasons including political instability, social influences, poor economic conditions, and social factors such as marriage and poverty in their home countries. When they arrive in Cape Town, they face many obstacles in securing employment because of either their nationality or documentation status. They are also vulnerable due to lack of basic needs, living in overcrowded homes, and being in informal settlements where they build temporary shelters. To overcome the challenges they face, they engage in different livelihood strategies such as accessing free government clinics or hospitals for their healthcare. They are dependent on their spouses for support and engage in part-time employment. Besides, they have had limited information about any government or non-governmental organisations that provide support for unemployed black female migrant youth. The need for well-established social networks for unemployed black female migrants, where they can be received and assisted in integrating into society through legitimate channels, is relevant. There need to be centres that offer free English-language training for migrants who are not conversant in English. Established non-governmental organisations or government agencies need to provide facilities that could assist undocumented immigrants who have prolonged their stay in Cape Town. There is also a need to establish support centres that specifically target unemployed black female immigrants. The South African government should enforce sensitization and educate the public and stakeholders about the legitimacy of asylum-seeker permits issued to immigrants. If implemented in conjunction with policy measures, this could increase black female immigrant youth's ability to secure employment. The enforcement of the development of entrepreneurial skills programmes, which specifically vi target unemployed black female youth migrants in Cape Town, is another potentially beneficial strategy.